The Effects of Education on Tobacco Consumption: A Panel Data Analysis - Nkomo, Nomusa Yolanda; Adanlawo, Eyitayo Francis (Journal of Ecohumanism, 2024)
This study tests the hypothesis that acquiring more education improves health by reducing smoking habits. The study investigates whether higher levels of education influence smokers' behaviour or not. A panel dataset from South Africa's National Income Dynamic Survey (2008–2017) was used as a data collection source. The study employs a logistic model to conclude that people in South Africa with more education are less likely to smoke than those without education. Also noteworthy is the discovery that individuals with mental health-related behavioural disorders are more likely to smoke as a form of self-medication. Our results are particularly significant for policymakers since they demonstrate that education reduces the likelihood of smoking. These findings indicate the need for increased government support for educational opportunities in South Africa. In the long run, the population health of a country may benefit from free public education. Programs aimed at reducing smoking ought to focus on individuals with lower levels of education, younger people, and city dwellers because they are more likely to be engaged in smoking.